The Impact of Teacher Training Programs on the Implementation of Inclusive Education for Children with Autism in Urban Public Schools in the United States - Anna Marie Johnson; Sarah Williams; James Edward Wilson (Research and Advances in Education, 2024)
Inclusive education has gained prominence as a means to ensure equal learning opportunities for all children, including those with autism. This study delves into the impact of teacher training programs on the implementation of inclusive education for children with autism in urban public schools in the United States. The research is grounded in the hypothesis that well-designed teacher training programs are pivotal in equipping educators with the knowledge, skills, and attitudes necessary to effectively teach and support students with autism in inclusive settings. To investigate this, the study employed a mixed-methods approach, combining quantitative surveys and qualitative interviews. The surveys were administered to a sample of teachers from urban public schools before and after participating in a specific teacher training program focused on inclusive education for children with autism. The interviews were conducted to gain deeper insights into the teachers’ experiences and perceptions of the training’s impact on their classroom practices. The findings reveal a significant positive impact of the teacher training programs on teachers’ self-efficacy and attitudes towards inclusive education. Teachers reported an increased confidence in their ability to adapt teaching strategies to meet the diverse needs of students with autism. Additionally, the study highlights the importance of ongoing professional development and support for teachers to sustain and enhance the implementation of inclusive practices. This research contributes to the growing body of literature on inclusive education and provides valuable implications for policymakers, educators, and training program developers. It underscores the necessity of comprehensive and continuous teacher training programs to foster an inclusive educational environment for children with autism in urban public schools.